Monocyclic β-lactam and unexpected oxazinone formation: synthesis, crystal structure, docking studies and antibacterial evaluation. (2nd September 2016) - Aneja, Babita; Irfan, Mohammad; Hassan, Md. Imtaiyaz; Prakash, Amresh; Yadava, Umesh; Daniliuc, Constantin G.; Zafaryab, Md.; Rizvi, M. Moshahid A.; Azam, Amir; Abid, Mohammad
Abstract: Novel monocyclic β-lactam derivatives bearing aryl, phenyl and heterocyclic rings were synthesized as possible antibacterial agents. Cyclization of imines (3h, 3t ) with phenylacetic acid in the presence of phosphoryl chloride and triethyl amine did not afford the expected β-lactams. Instead, highly substituted 1, 3-oxazin-4-ones (4h, 4t ) were isolated as the only product and confirmed by single crystal X-ray analysis of4t . The results of antibacterial activity showed that compound4l exhibited considerable antibacterial activity with MIC and MBC values of 62.5 µg/mL against Klebsiella pneumoniae . Cytotoxicity assay on Chinese Hamster Ovary (CHO) cell line revealed non-cytotoxic behavior of compounds4d, 4h, 4k and4l up to 200 μg/mL conc. Molecular docking was performed for compound4l with penicillin binding protein-5 to identify the nature of interactions. The results of both in silico and in vitro evaluation provide the basis for compound4l to be carried as a potential lead molecule in the drug discovery pipeline against bacterial infections.